(untitled) (Docentes 2.0 Journal, 2024)
In an innovative environment, using business simulators in academic preparation encourages the application of theory in the development of experiential learning related to student satisfaction and academic performance. Analyze the relationship between the level of satisfaction and experiential learning in university students based on their performance. The research was based on the pragmatic paradigm, convergent mixed method, concurrent triangulation design, and concurrent type. A sample of 94 university students aged 18 – 35 from the Business Laboratory course was evaluated through a questionnaire using the Level of Reflective Thinking Scale based on Kolb’s Experiential Learning Cycle and the Student Satisfaction Scale. A semi-structured interview is implemented with students enrolled in the different sections and a review of notes from the corresponding course. In this sense, implementing simulators in academic programs impacts student performance and satisfaction, although they face challenges such as lack of teacher preparation and economic limitations. A significant correlation of .001 was identified between the analyzed variables, resulting in student satisfaction related to using business simulators based on experiential learning and its relationship with academic performance.